2011
DOI: 10.4103/1658-354x.76510
|View full text |Cite
|
Sign up to set email alerts
|

Combined parecoxib and I.V. paracetamol provides additional analgesic effect with better postoperative satisfaction in patients undergoing anterior cruciate ligament reconstruction

Abstract: Background:Adequacy of postoperative analgesia is one of the most important factors that determine early hospital discharge and patients’ ability to resume their normal activities postoperatively. The optimal non-opioid analgesic technique for postoperative pain management would reduce pain and enhance patient satisfaction, and it also facilitates earlier mobilization and rehabilitation by reducing pain-related complications after surgery. The aim of this study was to evaluate the analgesic efficacy of intrave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Several RCTs have compared the efficacy of PAR with IV PRO or paracetamol for post‐operative analgesia in various surgical settings, including combination therapy with PAR and PRO or paracetamol vs. either agent alone . Systematic reviews that compared NSAIDs/COX‐2 inhibitors, paracetamol, and their combinations for treatment of post‐surgical pain concluded that the combination may provide additional analgesic efficacy than either drug alone, although evidence for additive or synergistic effects of most combination regimens is lacking .…”
Section: Discussionmentioning
confidence: 99%
“…Several RCTs have compared the efficacy of PAR with IV PRO or paracetamol for post‐operative analgesia in various surgical settings, including combination therapy with PAR and PRO or paracetamol vs. either agent alone . Systematic reviews that compared NSAIDs/COX‐2 inhibitors, paracetamol, and their combinations for treatment of post‐surgical pain concluded that the combination may provide additional analgesic efficacy than either drug alone, although evidence for additive or synergistic effects of most combination regimens is lacking .…”
Section: Discussionmentioning
confidence: 99%
“…A total of 27 RCTs with 2840 participants were included [ 14 , 15 , 24 – 48 ], with between 15 and 310 participants receiving intravenous parecoxib per study. There were 15 RCTs on knee and hip arthroplasty [ 14 , 15 , 24 27 , 29 31 , 33 , 36 , 42 , 46 – 48 ], 5 on lumbar spine surgery [ 32 , 38 , 40 , 41 , 44 ], 2 on anterior cruciate ligament reconstruction [ 34 , 37 ], 2 on bunionectomy [ 39 , 45 ], and 3 on other orthopedic surgery [ 28 , 35 , 43 ]. The control groups included placebo (23 trials), ketorolac (3 trials), paracetamol (3 trials), and celecoxib (1 trial).…”
Section: Resultsmentioning
confidence: 99%
“…For future research, we recommend evaluating the behavior of paracetamol and ketorolac in combination with other analgesics families in different age populations; this would allow us to open our knowledge on the subject of multimodal analgesia and preemptive analgesia, so we recommend continuing these studies [41][42][43].…”
Section: Discussionmentioning
confidence: 99%